The impact of air humidity on the operation of proton exchange membrane fuel cells determined using dynamic electrochemical impedance spectroscopy. (1st May 2020) - Janicka, E.; Mielniczek, M.; Gawel, L.; Darowicki, K.; Landowska, P.
Abstract: This paper describes the changes in the fuel cell impedance across a range of current loads and humidity changes. The changes of each equivalent circuit parameters representing specific processes occurring in fuel cells, as a function of humidity and current changes, were determined. Within the combined scope of current and humidity, the optimal working conditions of the cells were determined, corresponding to the lowest impedance values. The influence of humidity on the charge transfer resistance behavior and the Warburg coefficient for varying current load values were analyzed in detail.